(untitled) (Damascus University Journal for engineering sciences, 2021)
Developing a national brand (nation branding) topic is a top priority in geopolitics and media worldwide, especially for developing countries. Nowadays countries strive hard to strategically position themselves, attract foreign investment, promote tourism and exports in unprecedented marketing environments. Nation branding strengthens the sense of citizenship and belonging among citizens of countries and opens horizons of interconnection with other countries. The study defines related terminology and outlines the most prominent stops in the course of nation branding development. It also goes through the most important strategies for developing and localizing nation branding (positioning of nation branding), as well as the impact of the phrase “Country of Origin-COO” and the classifications of “Country Brand Index- CBI”, without losing sight of the role graphic design plays in this process. Lastly, the study includes an analysis of two models in an attempt to apply theory in real- life settings and it concludes with a group of findings. The objective of the study is to determine the role of graphic design and its different uses and contributions to the development of nation branding. Drawing on that, graphic design utilizes all resources of countries, such as, poets, writers, artists, geographical nature, livestock, industry, tourism, history, among others. Graphic design makes use of this rich incubator to generate visual elements on renewed basis. Research Problem: Even though nation branding is a hot topic, people on the local level are not deeply aware of it; its consequences can only be measured on the long run. What’s more, Arabic content, academic research and applied studies fall short of the growing concern for nation branding. Significance: Nation branding is a relatively new concept that contributes to changing and directing ideas and opinions about countries by rectifying related assumptions. This significance increases in times of war and conflict, during which media and some special events have major influence over perceptions and considerations, which might be false or politicized with possible negative implications.